2011
DOI: 10.1097/dad.0b013e3181fb5bc7
|View full text |Cite
|
Sign up to set email alerts
|

Lack of BRAFV600E Mutations in Giant Congenital Melanocytic Nevi in a Chinese Population

Abstract: Giant congenital melanocytic nevi (CMNs) are at an increased risk for malignant transformation. To explore the mutation frequencies of BRAF(V600E) (V-raf murine sarcoma virus oncogene homolog B1) and NRAS (neuroblastoma ras viral oncogene homolog) codon 61 in CMNs of Chinese, we selected 55 paraffin-embedded tissue blocks, including 37 cases of medium CMNs (1.5-20cm) and 18 cases of giant CMNs (>20 cm). Direct sequencing was performed to detect the BRAF(V600E) and NRAS codon 61 mutations. The BRAF(V600E) mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 24 publications
3
33
0
Order By: Relevance
“…Rare incidences of concurrent NRAS and BRAF mutations have been described, for example in two cases of melanoma in a large series (0·7%), in one of 15 nodular melanomas, in one of 14 melanomas, in four of 60 cases of melanoma arising within an existing naevus, and in 1·6% in a large series of 484 melanomas; however in this last study, cloning of a single NRAS/BRAF mutant cell line revealed the mutations were mutually exclusive at single‐cell level . Although a number of studies have adopted sensitive techniques for NRAS/BRAF mutational analysis over Sanger sequencing for their improved ability to detect mutant alleles at low frequency, many studies have relied on Sanger sequencing alone . In our study, the use of at least two highly sensitive methods of mutation detection, and the unbiased genotyping strategy, can confirm mutual exclusivity of these mutations in CMN.…”
Section: Discussionmentioning
confidence: 66%
“…Rare incidences of concurrent NRAS and BRAF mutations have been described, for example in two cases of melanoma in a large series (0·7%), in one of 15 nodular melanomas, in one of 14 melanomas, in four of 60 cases of melanoma arising within an existing naevus, and in 1·6% in a large series of 484 melanomas; however in this last study, cloning of a single NRAS/BRAF mutant cell line revealed the mutations were mutually exclusive at single‐cell level . Although a number of studies have adopted sensitive techniques for NRAS/BRAF mutational analysis over Sanger sequencing for their improved ability to detect mutant alleles at low frequency, many studies have relied on Sanger sequencing alone . In our study, the use of at least two highly sensitive methods of mutation detection, and the unbiased genotyping strategy, can confirm mutual exclusivity of these mutations in CMN.…”
Section: Discussionmentioning
confidence: 66%
“…have shown in a retrospective study, that malignization occurred only in nevi with a diameter ≥20 cm. 10-19 25 Moreover, the ease of obtaining the diameter of the nevus during physical examination, the accuracy of measurement in centimeters and the applicability of this classification to both adults and children make it useful for the medical practice. 18 …”
Section: Classificationmentioning
confidence: 99%
“…Activation of these pathways following somatic mutations in the RAS and RAF genes might represent one of the initial steps in the development of melanocytic naevi [66]. The BRAF oncogene on chromosome 7Q34 is commonly mutated in over 70% of MMs [67], but this mutation is absent in giant congenital melanocytic naevi [68]. MM with multiple naevi and BRAF mutation occur more frequently at a younger age and on intermittently sun-exposed sites [69].…”
Section: Germline and Somatic MM Mutationsmentioning
confidence: 99%
“…Blue naevi, Spitz melanocytomas, congenital melanocytic naevi, and uveal MM do not or rarely contain BRAF mutations [68]. By contrast, they contain other mutations such as in the NRAS or HRAS genes [77].…”
Section: Germline and Somatic MM Mutationsmentioning
confidence: 99%